Synthesis, physical-chemical properties, antimicrobial and antifungal activity of some 2-(2-((5-(adamantane-1-yl)-4-R-1,2,4-triazole-3-yl)thio)acetyl)-N-R1–hydrazine-carbothioamides - V. M. Odyntsova; A. M. Kamyshny; N. N. Polischuk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2017)
Special attention of pharmaceutical scientists is attracted to the creation of new potential substances. They select natural heterocyclic molecules that exhibit various types of pharmacological activity as basic structures. Adamantane derivatives, as well as a number of other framework compounds, in the vast majority are biologically active substances. This fact causes interest to the given classes of organic compounds as potential sources for the development of new drugs. Due to the high pharmacological action of 1,2,4-triazole derivatives, the combination of adamantane and 1,2,4-triazole in one molecule can lead to the formation of high-level pharmacological substances.